"Moving Toward Healthy": Insights Into Food Choices of Mothers in Residential Recovery. (29th November 2016) - Wall-Bassett, Elizabeth D.; Robinson, Michael A.; Knight, Sharon
This study utilized participatory and potentially empowering qualitative research methods of photo-elicitation and face-to-face interviews to investigate food choices of mothers living with their children in a residential substance use disorder recovery program. Face-to-face interviews were conducted with nine women (25–40 years) living in a residential substance use disorder recovery program in the Southeastern United States. Each audio recorded and transcribed interview was coded individually before collectively developing a consensual version of the codebook and identifying themes. The recovering women in this study expressed a new or renewed desire to "eat healthy" and voiced concerns about the nutritional value of foods. Food choices were influenced by their children's nutritional needs and food preferences, their own food preferences and habits, the financial resources available to them, their personal food preparation self-efficacy and skills, and the limitations inherent in residential recovery. Understanding food choices benefits both recovering parents and their children.